Clinical study on complicated presentations of groin hernias - S., Hariprasad; Srinivas, Teerthanath (International Journal of Research in Medical Sciences, 2017)
Background: Groin hernia is a very common type abdominal wall hernia encountered in surgical practice. Irreducibility, obstruction and strangulation are its commonest complications which usually presents as acute emergencies. Emergency repair of complicated hernias is associated with poor prognosis and a high rate of post-operative complications even with better care, improved anaesthetic management and advanced surgical techniques. The aim of this study was to determine the various modes of presentation, clinical finding, diagnostic and therapeutic strategies and to evaluate the postoperative outcome in complicated groin hernia surgeries in our set up. Methods: The study was carried out among 40 patients of groin hernia, who had complicated clinical presentation like irreducibility, strangulation and obstruction in the department of general surgery, during the period from March 2012 to June 2014. Patients were enrolled into the study after proper consent for detailed clinical examination, investigation and subsequent treatment. The Data obtained included demographic characteristics, presentation, operative findings and outcome. The patients were followed up for immediate and late complications for once a week for 1 months, once every month for the next 6 months. After data collection, analysis was done with help of by SPSS software version 21. Results: A total of 40 groin hernia patients with complicated presentation were evaluated during the study period. Among these cases 38 cases had inguinal hernias and two cases had femoral hernia. Majority of the patients were in 5th and 6th decade. Complicated presentation of groin hernia was commonly seen in males (95%) than in females (5%) with male to female ratio of 19:1. Inguinal hernia complications were seen predominantly in males and femoral hernia complications in females. Right sided hernias were more common. Incarceration was the commonest complication seen in 70% of case followed by strangulation (30%). Incarceration was high (17.5%) in the age group of 64-73 years and 44 - 53 years. Strangulation was high in the age group of 54-63 years. The duration of hernia varied for 1-2 years in 42.5% of cases and 3-6 years in 27.5% of cases. Majority of the patients (30%) presented with localized groin pain, vomiting, constipation and abdominal distension. All patients presented with swelling in the inguinoscrotal region, which was tender, and there was no impulse on coughing and 35% of patients had cardiorespiratory illness. Majority of the cases (34 numbers) were operated as emergency procedure. Viable bowel was seen in 77.5% of cases. Bowel resection and end-to-end anastomosis was done in all cases of non-viable bowel and orchidectomy in atrophied and gangrenous testis. The commonest postoperative complication encountered in the study was wound infection (22.5%) and scrotal seroma (17.50%). There was no evidence of recurrence in any of the operated cases. Conclusions: Complicated presentations of groin hernias like, incarceration and strangulation are seen in low and middle socio-economic category of people and may be associated with chronic illness. The cumulative risk of strangulation increases with time and type of hernias. Timely diagnosis and prompted surgical repair is essential to prevent the complications.